2002
DOI: 10.1056/nejmoa021274
|View full text |Cite
|
Sign up to set email alerts
|

Heparin plus Alteplase Compared with Heparin Alone in Patients with Submassive Pulmonary Embolism

Abstract: When given in conjunction with heparin, alteplase can improve the clinical course of stable patients who have acute submassive pulmonary embolism and can prevent clinical deterioration requiring the escalation of treatment during the hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
373
0
28

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 885 publications
(410 citation statements)
references
References 30 publications
9
373
0
28
Order By: Relevance
“…In contrast patient with elevated cardiac markers may require immediate triage for ICU, urgent thrombolysis [18] and catheter embolectomy [19] or open surgical embolectomy [20]. Kostrubiec et al, 2007 [21] found that persistent elevation of NT-pro BNP 24 hours after diagnosis (reduction of less than 50% from initial values) predicts higher mortality at thirty days.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast patient with elevated cardiac markers may require immediate triage for ICU, urgent thrombolysis [18] and catheter embolectomy [19] or open surgical embolectomy [20]. Kostrubiec et al, 2007 [21] found that persistent elevation of NT-pro BNP 24 hours after diagnosis (reduction of less than 50% from initial values) predicts higher mortality at thirty days.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Our results were in agreement with those in previous reports. Although right ventricular dysfunction has recently drawn attention as a prognostic factor of APTE, [19][20][21][22][23] the relationship between thrombolysis and outcome in patients with right ventricular dysfunction was not evaluated in the present study because not all of the study subjects underwent echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we did not investigate the association between right ventricular function and the clinical outcomes, which was done in previous reports. [19][20][21][22][23] Finally, this study included patients for 25 consecutive years. During this period there have been significant developments in APTE management: more effective tools such as inferior vena cava filters 26,27 and venous ultrasounds 28,29 have recently become available.…”
Section: Study Limitationsmentioning
confidence: 99%
“…The authors claim that this study proves the benefit of systemic thrombolysis in well-defined patients and that thrombolysis should therefore be considered routinely as an option in those patients [40]. Opponents argue that the difference in outcome was exclusively due to the frequency of secondary thrombolysis within the first 4 days and to a treatment escalation which had no objective measure but was left entirely to the discretion of the attending physician.…”
Section: Systemic Thrombolysismentioning
confidence: 93%
“…Konstantinides et al [40]conducted a randomized controlled trial from 1997 to 2001, enrolling 256 patients with submassive PE at 49 study sites. Hemodynamically stable patients with significant right ventricular dysfunction were randomized to receive either 100 mg of alteplase over 2 h or placebo.…”
Section: Systemic Thrombolysismentioning
confidence: 99%